2022
DOI: 10.3390/plants11192549
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Feed Quality Performance of Napier Grass (Cenchrus purpureus) Genotypes Growing under Different Soil Moisture Levels

Abstract: In the semi-arid and arid environments of Sub-Sharan Africa, forage availability throughout the year is insufficient and highly limited during the dry seasons due to limited precipitation. Thus, the identification of drought stress-tolerant forage cultivars is one of the main activities in forage development programs. In this study, Napier grass (Cenchrus purpureus), an important forage crop in Eastern and Central Africa that is broadly adapted to produce across tropical environments, was evaluated for its wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…1 Sources: Ferraris, 1980 ; Brown et al., 1988 ; Anindo and Potter, 1994 ; Aroeira et al., 1999 ; Filho et al., 2000 ; Huque et al., 2001 ; Gwayumba et al., 2002 ; Islam et al., 2003 ; Aganga et al., 2005 ; Goorahoo et al., 2005 ; Chen et al., 2006 ; Castillo et al., 2010 ; Das et al., 2010 ; Bureenok et al., 2012 ; Danes et al., 2013 ; Ferreira et al., 2013 ; Halim et al., 2013 ; Gomide et al., 2015 ; Amin et al., 2016 ; Aswanimiyuni et al., 2018 ; Garcez et al., 2018 ; Gusmao et al., 2018 ; Habte et al., 2022 ; Ito et al., 1988 ; Kaitho and Kariuki, 1998 ; Kariuki et al., 1998 ; Kariuki et al., 1999 ; Kozloski et al., 2003 ; Kozloski et al., 2005 ; Khairani et al., 2013 ; Knoll et al., 2013 ; Kabirizi et al., 2015 ; Khota et al., 2018 ; Lounglowan et al., 2014 ; Manyawu et al., 2003a ; Manyawu et al., 2003b ; Manyawu et al., 2003c ; Magalhães et al., 2010 ; Muinga et al., 1992 ; Muinga et al., 1993 ; Nsahlai et al., 2000 ; Muia et al., 2001a ; Muia et al., 2001b ; Muyekho et al., 2015 ; Parsons et al., 2012 ; Pieterse and Rethman, 2002 ; Rahman et al., 2010 ; Rahman et al., 2013 ; Rahman et al., 2013 ; Rahman et al., 2015 ; Ruiz et al., 1992 ; Rao et al., 1993 ; …”
Section: Current Napier Grass Production Systemsunclassified
See 3 more Smart Citations
“…1 Sources: Ferraris, 1980 ; Brown et al., 1988 ; Anindo and Potter, 1994 ; Aroeira et al., 1999 ; Filho et al., 2000 ; Huque et al., 2001 ; Gwayumba et al., 2002 ; Islam et al., 2003 ; Aganga et al., 2005 ; Goorahoo et al., 2005 ; Chen et al., 2006 ; Castillo et al., 2010 ; Das et al., 2010 ; Bureenok et al., 2012 ; Danes et al., 2013 ; Ferreira et al., 2013 ; Halim et al., 2013 ; Gomide et al., 2015 ; Amin et al., 2016 ; Aswanimiyuni et al., 2018 ; Garcez et al., 2018 ; Gusmao et al., 2018 ; Habte et al., 2022 ; Ito et al., 1988 ; Kaitho and Kariuki, 1998 ; Kariuki et al., 1998 ; Kariuki et al., 1999 ; Kozloski et al., 2003 ; Kozloski et al., 2005 ; Khairani et al., 2013 ; Knoll et al., 2013 ; Kabirizi et al., 2015 ; Khota et al., 2018 ; Lounglowan et al., 2014 ; Manyawu et al., 2003a ; Manyawu et al., 2003b ; Manyawu et al., 2003c ; Magalhães et al., 2010 ; Muinga et al., 1992 ; Muinga et al., 1993 ; Nsahlai et al., 2000 ; Muia et al., 2001a ; Muia et al., 2001b ; Muyekho et al., 2015 ; Parsons et al., 2012 ; Pieterse and Rethman, 2002 ; Rahman et al., 2010 ; Rahman et al., 2013 ; Rahman et al., 2013 ; Rahman et al., 2015 ; Ruiz et al., 1992 ; Rao et al., 1993 ; …”
Section: Current Napier Grass Production Systemsunclassified
“…Water also affects the quality of Napier grass varieties ( Habte et al., 2022 ). These authors reported that Napier grass NDF, ADF, and lignin decreased but CP and ME increased under water stress conditions.…”
Section: Current Napier Grass Production Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its preference is based on its ability to adapt to high temperature and radiation; tolerate drought and capacity to grow in sandy soils (Carballo et al, 2019 ). This grass is highly valued by farmers particularly for cattle feed in semi-arid regions (Habte et al, 2022 ). Despite its preference as a feed resource in SA, Weeping lovegrass is a C 4 perennial grass that has threatened natural ecosystems globally (Roberts et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%